Analysis Of Training And Career Development On Job Satisfaction Of Inpatient Nurses At Gambiran Hospital Kediri City - Laily Wulandari; Yasmin Namira Maulida; Titin Susanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Human resources, particularly nurses have key roles in ensuring the quality of hospital services. Training and career development are important strategies in improving the competence and job satisfaction of healthcare workers. This study aims to analyze the effect of training and career development on job satisfaction of inpatient nurses at Gambiran Regional General Hospital, Kediri City. Observational cross-sectional survey was was conducted at Gambiran Regional General Hospital, Kediri City, in June 2025. The study population was 117 nurses while the sample was 92 inpatient nurses, selected using a simple random sampling technique. The research variables were training, career development, and job satisfaction. Data were analyzed using the Spearman Rho test and the Generalized Linear Model (GLM).The analysis showed that training significantly influenced job satisfaction with a correlation value of 0.362 (sig = 0.000), and career development also had a significant effect with a correlation value of 0.464 (sig = 0.000). The GLM test showed that career development (sig= 0.003; B = 0.463) and training (sig = 0.027; B = 0.295) both significantly influenced job satisfaction. Training and career development positively contributed to nurses' job satisfaction. Appropriate training improved skills and confidence, while career development created hope and motivation for a better future on the job. These results indicate that hospital management needs to strengthen training and career development programs to improve nurse job satisfaction and performance.